2014
DOI: 10.1586/14737140.2015.978294
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNA in head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide. Evidence suggests that miRNAs play an important role in progression, recurrence, metastasis and postoperative survival of HNSCC. Studies have investigated the utility of miRNAs as diagnostic/prognostic tools and as potential therapeutic targets and biomarkers that may improve the management and outcomes of HNSCC. The aim of this article is to review the current literature on aberrant expression profiles of miRNAs in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 129 publications
0
18
0
Order By: Relevance
“…Several recent studies have shown differential miRNA expression in HNSCC (Jamali et al., ; Koshizuka et al., ; Masood, Kqueen, & Rajadurai, ). Barker et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have shown differential miRNA expression in HNSCC (Jamali et al., ; Koshizuka et al., ; Masood, Kqueen, & Rajadurai, ). Barker et al.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased expression of hsa‐miR‐200b‐5p and hsa‐miR‐29c‐3p in tumor was found to be associated with higher tumor grade, and decreased expression of hsa‐miR‐29c‐3p in adjacent tumor tissue was associated with worse survival and with worse relapse‐free survival. These miRNA profiles were found to correlate with disease etiology, pathogenesis, metastasis, and recurrence of HNSCC (Barker et al., ; Chen et al., ; Hui et al., ; Masood et al., ). Thus, studies till date suggest distinct miRNA profiles may have potential as diagnostic and prognostic markers in HNSCC but these observations still need to be validated in larger cohorts and in different ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are noncoding RNAs derived from loci in the homeobox (HOX) gene clusters 21 in human chromosomes 17q21.32 (MIR196A1), 12q13.13 (MIR196A2) and 7p15.2 (MIR196B), among which the mature microRNAs miR-196a1 and a2 are identical and miR-196b differs by one nucleotide. As individual microRNAs can regulate multiple genes 17, 18 including those encoding transcription factors, we also investigated the potential contribution of transcriptional control by analysis of ANXA1 promoter activity.…”
Section: Introductionmentioning
confidence: 99%
“…11 According to several studies miRNAs expression profile is also emerging among the best markers for diagnosis, staging, and treatment of cancer, including head and neck squamous cell carcinoma. [12][13][14] In particular, our group together with others has observed a correlation between the expression of specific miRNAs and outcome of head and neck squamous cell carcinoma patients. 12,[14][15][16] Here, we aimed at identifying key alterations of miRNAs expression occurring in tumor-surrounding mucosa (referred to as 'peritumoral' mucosa hereafter) from head and neck squamous cell carcinoma patients, which predict local recurrence.…”
mentioning
confidence: 99%